Understanding Global Defense Budgeting Dynamics: A Systematic Literature Review on Economic and Geopolitical Factors - Muchamad Bachtiar; Irdam Ahmad; Zainal Abidin Sahabuddin; Trismadi (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Defense budgeting plays a critical role in shaping a nation's strategic and military capabilities, reflecting its global positioning and priorities. It is influenced by a complex intersection of global politics, security concerns, and economic factors. Understanding these dynamics is crucial for guiding national policies and strategies.Purpose: This study aims to analyze the intricate factors shaping military expenditures globally, with a focus on understanding the role of Gross Domestic Product (GDP) growth, geopolitical tensions, and international political dynamics.Design/methodology/approach: The research employs a systematic literature review (SLR) guided by the PRISMA protocol to synthesize insights from existing studies. Utilizes Scopus-indexed journals to ensure the quality and reliability of the literature.Findings/Results: The findings highlight GDP growth as a central determinant of military expenditure, influenced by geopolitical interdependencies and regional dynamics. Theoretical frameworks, such as "Realist Theory" and "Neoclassical Theory," frequently appear in the literature, emphasizing the interplay between economic and defense paradigms. Conclusion: Defense budgeting is shaped by multidimensional factors, requiring further research with broader data sources and regional focus.Originality/value (State of the art): This study provides a systematic synthesis of defense expenditure dynamics, bridging gaps in economic and geopolitical perspectives. Keywords: defense budget, military expenditure, Gross Domestic Product (GDP), defense economics, Systematic Literature Review (SLR)